Shielding from external magnetic fields by rotating magnetic conducting cylindrical shells. Issue 2 (2nd March 2015) - Slawomir Wiak, Professor; Ziolkowski, Marcin; Gratkowski, Stanislaw
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – In many different engineering fields often there is a need to protect regions from electromagnetic interference. According to static and low-frequency magnetic fields the common strategy bases on using a shield made of conductive or ferromagnetic material. Another screening technique uses solenoids that generate an opposite magnetic field to the external one. The purpose of this paper is to discuss the shielding effect for a magnetic and conducting cylindrical screen rotating in an external static magnetic field. Design/methodology/approach – The magnetic flux density is expressed in terms of the magnetic vector potential. Applying the separation of variables method analytical solutions are obtained for an infinitely long magnetic conducting cylindrical screen rotating in a uniform static transverse magnetic field. Findings – Analytical formulas of the shielding factor for a cylindrical screen of arbitrary conductivity and magnetic permeability are given. A magnetic Reynolds number is found to be an appropriate indication of the change in magnetic field inside the screen. Useful simplified expressions are presented. Originality/value – This paper treats in a qualitative way the possibility of static magnetic field shielding by using rotating conducting magnetic cylindrical screens. Analytical solutions are given. If the angular velocity is equal to zero or the relative permeability of the shield is equal to one the shielding factor has forms well known from literature.